DNA N6-Methyladenine Modification in Eukaryotic Genome - Li, Hao; Zhang, Ning; Wang, Yuechen; Xia, Siyuan; Zhu, Yating; Xing, Chen; Tian, Xuefeng; Du, Yinan (Frontiers in Genetics, 2022)
DNA methylation is treated as an important epigenetic mark in various biological activities. In the past, a large number of articles focused on 5mC while lacking attention to N6-methyladenine (6mA). The presence of 6mA modification was previously discovered only in the prokaryote’s genome. Recently, with the development of detection technologies, 6mA is found in several eukaryotes including protozoans, metazoans, plants, and fungi. The importance of 6mA in prokaryotes and single-celled eukaryotes has been widely accepted. However, due to the incredibly low density of 6mA and restrictions on detection technologies, the prevalence of 6mA and its role in biological processes in eukaryotic organisms are highly debated. In this review, we first summarize the advantages and disadvantages of 6mA detection methods. Then, we conclude the existing reports on the prevalence of 6mA in eukaryotic organisms. Next, we highlight possible methyltransferases, demethylases, and the recognition proteins of 6mA. In addition, we summarize the functions of 6mA in eukaryotes. Last but not least, we summarize our point of view and put forward the problems that need further research.